1989
DOI: 10.1177/089198878900200209
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Between Cognitive Performance and Daily Functioning in Elderly People

Abstract: The Mini-Mental State Examination (MMSE) is widely used to detect dementia, but the diagnosis of dementia also depends on a decline in the level of daily functioning. Little is known about the relationship between performance on the MMSE and daily living abilities. This relationship was investigated in this study of an elderly population by comparing scores on the MMSE with those on both a direct assessment of everyday tasks and an indirect questionnaire about activities of daily living and physical self-maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 17 publications
1
35
2
Order By: Relevance
“…We found that poorer physical function coexisted with cognitive impairment, which is compatible with previous observations [1][2][3][4][5][6][7][8][9] . After the adjustment for muscle mass and other possible confounding factors, the difference in physical function performance between the cognitively impaired and nonimpaired groups persisted though the difference had narrowed considerably, illustrating the residual confounding effect of the covariates entered into the regression model, namely muscle mass, age, comorbidities and physical activity level.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that poorer physical function coexisted with cognitive impairment, which is compatible with previous observations [1][2][3][4][5][6][7][8][9] . After the adjustment for muscle mass and other possible confounding factors, the difference in physical function performance between the cognitively impaired and nonimpaired groups persisted though the difference had narrowed considerably, illustrating the residual confounding effect of the covariates entered into the regression model, namely muscle mass, age, comorbidities and physical activity level.…”
Section: Discussionsupporting
confidence: 82%
“…tive decline was associated with functional disability [1][2][3][4][5] . Lower cognitive function was also associated with poor physical performance in gait speed, standing balance and chair stand tests [6,7] .…”
mentioning
confidence: 99%
“…Its clinical progression would allow implementing therapeutic strategies optimizing the executive functions in daily life complex activities Several studies describe the functional cognitive association and its mutual correlation (Rubial-Álvarez, De Sola, Machado, 2013;Warren, 1989). Complex functional impairment can precede cognitive impairment in aging as well as in some neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…activities of daily living; functional ability; executive functioning; dementia; Alzheimer's disease It has been well established that tests of executive functioning are useful in characterizing frontal lobe brain lesions and various forms of dementia (Kramer et al, 2005;Kennedy, 2004;Razani, Boone, Miller, Lee, & Sherman, 2001; Walker, Meares, Sachdev, & Bodaty, Correspondence: Jill Razani, Ph.D., Department of Psychology, California State University, Northridge, 18111 Nordhoff Street, Northridge, CA 91330-8255, jill.razani@csun.edu, (818) 677-4623, (818) Most available studies have examined the relationship between ADLs and brief cognitive screening measures (e.g., MMSE) and ADLs (Vitaliano et al, 1984;Winograd, 1984) and have generally found strong correlations (Ford, Haley, Thrower, West, & Harrell, 1996;Reed, Jagust, & Seab, 1989;Warren et al, 1989). Similarly, few studies have examined the relationship between ADLs and larger neuropsychological test batteries.…”
Section: Introductionmentioning
confidence: 99%